2021
DOI: 10.1177/1556331621991825
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Price Transparency Policy and Evaluation of Hospital Compliance in Orthopedic Sports Medicine

Abstract: Background: In 2019, the Centers for Medicare and Medicaid Services (CMS) announced that beginning January 1, 2021, hospitals would be required to post pricing information in a usable format for patients via diagnosis-related group (DRG) or charge description master (CDM) sheets. Purpose/Questions: We hypothesized the new price transparency rule would pose challenges for many health care facilities. We therefore sought to find out how much pricing information was available before the rule took effect and how u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Procedure-specific information was also highly variable. Schultz et al, 15 investigating six common orthopedic sports medicine procedures, found that while 74%–86% of hospitals provided pricing information, only one of the six chosen procedures had pricing information available at 80% of hospitals, with the rest being reported by less than 27%–40% of hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Procedure-specific information was also highly variable. Schultz et al, 15 investigating six common orthopedic sports medicine procedures, found that while 74%–86% of hospitals provided pricing information, only one of the six chosen procedures had pricing information available at 80% of hospitals, with the rest being reported by less than 27%–40% of hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…18 Assessment of compliance to the price transparency rule is not straightforward, given that previous studies have assessed it differently. [11][12][13]16,20 To that end, we sought to use an inclusive definition, where hospitals that disclosed at least one price (and not necessarily prices of all commercial payers, Medicare Advantage, Medicaid, and cash prices along with de-identified minimum and maximum prices) were considered "compliant." Hospitals were considered to have disclosed prices if at least one negotiated payment was identified for the CPT codes and/or Medicare Severity Diagnosis Related Group (MS-DRG) codes encompassing mastectomy, lobectomy, WLE for cutaneous melanoma, partial colectomy, and prostatectomy in the Turquoise Health research dataset (supplemental eAppendix 1, available online at JNCCN.org).…”
Section: Discussionmentioning
confidence: 99%
“…10 Despite this, compliance with this price transparency rule has been low, ranging from 40% to 50%. [11][12][13][14] Prior cross-sectional investigations have shown that the majority of for-profit hospitals were noncompliant with at least one of the rule's requirements by failing to provide a chargemaster. 11,12,15,16 However, the impact of these studies on the care trajectories of patients with cancer in particular remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have assessed compliance among subsets of hospitals, including the 100 largest hospitals in terms of beds (Henderson & Mouslim, 2021) and gross revenue (Gondi et al, 2021), as well as select orthopedic hospitals (D'Amore et al, 2022; Schultz et al, 2021), hospitals with National Cancer Institute-designated cancer centers (Chino et al, 2021; Herb et al, 2022; Mathew et al, 2022a; Xiao et al, 2021), children's hospitals (Hayatghaibi et al, 2022), Association of American Medical Colleges-affiliated hospitals (Berkowitz et al, 2021), and U.S. News & World Report Honor Roll hospitals (Cram et al, 2021). Some studies also have examined price variation for specific procedures, including ophthalmological procedures (Berkowitz et al, 2021), pediatric tonsillectomy (Ayoub & Balakrishnan, 2022), sports medicine (Schultz et al, 2021), cancer prevention and treatment (Mathew et al, 2022b; Xiao et al, 2021), telemedicine (Wu et al, 2022) and cardiovascular tests and procedures (Oseran et al, 2022). Although providing timely information on early compliance, one limitation is that these sampled hospitals are disproportionately large, urban, and system-affiliated.…”
Section: Introductionmentioning
confidence: 99%